Marketing 5.0: Adaptation of Technology and Artificial Intelligence in Marketing Strategies - Wahyuni, Sri (Journal Research of Social Science, Economics, and Management, 2025)
The digital revolution has significantly transformed marketing strategies, particularly with the emergence of Marketing 5.0, which integrates advanced technology and artificial intelligence (AI) to create more personalized and efficient customer experiences. This study aims to analyze how companies adapt technology and AI in their marketing strategies to enhance competitiveness in the digital market. The research employs a qualitative method using a case study approach on several companies that have implemented AI-based technologies in their marketing strategies. Data was collected through in-depth interviews, observations, and document analysis. The findings indicate that AI in marketing enables content personalization, automation of customer interactions, and improved efficiency in data-driven decision-making. However, challenges such as limitations in digital infrastructure and organizational resistance to technological changes remain significant barriers. This study provides insights for marketing practitioners to better understand the role of technology in developing more innovative and adaptive strategies in the Marketing 5.0 era. The integration of AI and advanced technologies in marketing strategies underscores the importance for companies to continuously invest in digital infrastructure and foster a culture of innovation. Marketers must embrace these changes to stay competitive, yet overcome internal resistance and infrastructure limitations. Furthermore, businesses should focus on training and upskilling their workforce to handle new tools and techniques, thus ensuring long-term success in an increasingly technology-driven market landscape. Additionally, understanding the ethical and privacy implications of AI in customer data usage will be critical to maintaining consumer trust and loyalty.